Effectiveness of robot therapy in the management of behavioural and psychological symptoms for individuals with dementia: A systematic review and meta-analysis. (August 2021) - Ong, Yoke Chin; Tang, Arthur; Tam, Wilson
Abstract: Robot therapy presents a promising alternative in dementia care. However, its effectiveness has not been verified comprehensively. This systematic review and meta-analysis aim at evaluating the effectiveness of robot therapy in the management of behavioural and psychological symptoms for individuals with dementia. Studies assessing the effectiveness of robot therapy were identified using 10 academic research databases: CENTRAL, CINAHL, CNKI, The Cochrane Library, Embase, IEEE Xplore, MEDLINE, PubMed, Scopus, and ProQuest Dissertations & Theses. Additional references were identified from the reference lists of included studies and relevant reviews. Data extraction and risk of bias assessment were conducted independently by two review authors. Meta-analyses and subgroup analyses were performed and the heterogeneity of studies was examined. 18 published articles from 14 studies involving a total of 1256 participants were included. Participants with robot therapy had a significant decrease in agitation (SMD -0.38, 95% CI -0.66, −0.09; p = 0.01) and a significant increase in social interaction (SMD 0.49, 95% CI 0.01, 0.97; p = 0.04) while effects for depression, anxiety, cognitive status, and quality of life were not statistically significant. Results from this review show that robot therapy can effectively reduce agitation and increase social interactions for individuals with dementia. Future clinical practice should consider the potential of robot therapy as an option to be implemented into current dementia programmes. Further large-scale trials are required for the thorough investigation of different intervention formats and robot types, while considering potential confounding factors.